Effect of grain size on the static and dynamic mechanical properties of magnesium aluminate spinel (MgAl2O4). Issue 10 (August 2017) - Sokol, M.; Kalabukhov, S.; Shneck, R.; Zaretsky, E.; Frage, N.
Abstract: Samples of transparent polycrystalline spinel with average grain size varying from 0.14 to 170 μm were prepared by different sintering approaches. The effect of grain size on the flexural strength, hardness and Hugoniot elastic limit (impact loading) was investigated. It was found that values of hardness divided by three for samples with grain size in the 0.14–15 μm range were almost equal to the dynamic yield strength values, estimated based on the Hugoniot elastic limit. This led to the assumption that the onset of inelastic deformation at the Hugoniot elastic limit was brittle rather than ductile. The observed departure of the dynamic yield strength from the hardness divided by three value for ceramics with grain size >15 μm was associated with either impact-induced shear banding or twinning. The feasibility of such banding/twinning intervention in initiating inelastic deformation in the spinel is supported by the values of apparent Hall-Petch coefficients in the corresponding grain size domains.